Defective expression of p56lck in an infant with severe combined immunodeficiency. - Goldman, F D (1998)
Severe combined immune deficiency (SCID) is a heterogeneous disorder characterized by profound defects in cellular and humoral immunity. We report here an infant with clinical and laboratory features of SCID and selective CD4 lymphopenia and lack of CD28 expression on CD8(+) T cells. T cells from this patient showed poor blastogenic responses to various mitogens and IL-2. Other T cell antigen receptor- induced responses, including upregulation of CD69, were similarly inhibited. However, more proximal T cell antigen receptor signaling events, such as anti-CD3 induced protein tyrosine phosphorylation, phosphorylation of mitogen-associated protein kinase, and calcium mobilization were intact. Although p59fyn and ZAP-70 protein tyrosine kinases were expressed at normal levels, a marked decrease in the level of p56lck was noted. Furthermore, this decrease was associated with the presence of an alternatively spliced lck transcript lacking the exon 7 kinase encoding domain. These data suggest that a deficiency in p56lck expression can produce a SCID phenotype in humans.